Psychometric properties of the Portuguese version of the Achievement Emotions Questionnaire for Elementary School - Sanches, Cristina (2020)
The main purposes of the current research were to translate and adapt the Achievement Emotions Questionnaire – Elementary School (AEQ-ES) into Portuguese and to analyze its psychometric properties. A sample of 350 Portuguese third and fourth graders (aged 7 to 12 years) completed the Portuguese version of the AEQ-ES (AEQ-ES-P). As does the original version, the AEQ-ES-P measures students’ enjoyment, boredom, and anxiety toward mathematics in three academic settings: attending class, doing homework, and taking tests. Confirmatory factor analysis corroborated the hierarchical structure of the AEQ-ES-P, which was also invariant across gender and grades. The instrument also showed good reliability and temporal stability. Significant correlations were found in the expected direction between enjoyment, anxiety, and boredom, as well as between these emotions, students’ perceptions of competence, and intrinsic motivation toward mathematics, thus supporting the internal and external validity of the questionnaire. These results indicate that the AEQ-ES-P presents good psychometric properties and is suitable to measure the achievement emotions of Portuguese elementary-school children of the third and fourth grades in the domain of mathematics.